HER VOICE Newsletter fourth edition - Awinoh, Martha (CGIAR Initiative on Gender Equality, 2024)
We are proud to look back at an impressive body of research and innovations at the frontier of gender in agrifood systems research produced by an amazing cross-CGIAR and interdisciplinary HER+ team.